Diseño y selección de tecnología adecuada para tratamiento de aguas residuales domésticas, sector sur de Machala. - Carrillo Landín, Ángel (2017)
Due to the precarious sanitary conditions that are present in the southern sector of Machala and to the physical availability and predisposition of the population, the research topic of "DESIGN AND SELECTION OF ADEQUATE TECHNOLOGY FOR THE TREATMENT OF DOMESTIC RESIDUAL WATERS, SOUTHERN SECTOR OF MACHALA" , Which proposes to develop a guide for the treatment of wastewater through the system of stabilization ponds with technology adapted to the environment to improve the quality of life of its inhabitants. The type of direct discharges to canals and estuaries and their environmental contamination, area available for the operation of the treatment system and its environmental conditions were identified; The various technologies for its design were analyzed; Then the relevant technology for its implementation is proposed. The development of this research uses several research methods: conceptual, documentary and bibliographical, field, internet, analytical, synthetic and deductive, in which the techniques of documentary signing, observation, statistics and interviewing the inhabitants are considered. downloads. The research determines the feasibility of implementing the wastewater treatment system through stabilization ponds and the actions to use the areas and resources of the sector through techniques for design, construction, operation and maintenance that adapts to the conditions of the environment. South of Machala, especially the site where the area for the lagoons is located, being able to be used as a model to be implemented in other sectors of Machala.